The Influence of Compensation, Motivation, and Work Discipline on Employee Performance - Nurpribadi, Giri; Rulianti, Erina; Banteni, Fachrur Rozy Al (Yayasan Ilomata, 2024)
This study aims to analyze the effect of compensation, motivation, and work discipline on employee performance. The population of this study were all employees of PT Diamond Cold Storage which amounted to 80 people. The sampling technique in this study is a saturated sample or census because the entire population is used as a research sample. Research data collected through questionnaires that have been tested for validity and reliability. The results showed that compensation has a positive and significant effect on employee performance, meaning that the better the compensation provided, the more it will improve employee performance, motivation has a positive and significant effect on employee performance, meaning that the higher the motivation provided, the more it will improve employee performance, work discipline has a positive and significant effect on employee performance, meaning that the better the application of work discipline in the company, the more it will improve employee performance; and Compensation, motivation, and work discipline simultaneously have a significant effect on employee performance. The better the compensation, motivation, and implementation of work discipline together, the more it will improve overall employee performance. Policy Implications The company needs to formulate human resource policies related to the compensation system, motivation, and enforcement of work discipline so that employee performance can be optimized and company goals achieved.